Prevalence and profile of astigmatism in individuals availing ophthalmic services at Central Regional Referral Hospital, Gelephu, Bhutan: A cross-sectional, hospital-based study - Sangay Choden; Tshering Jamtsho; Indra P Sharma (Bhutan Health Journal)
Introduction: Astigmatism has been defined as a type of refractive error when parallel rays of light entering the eye are not focused at one point of the retina when accommodation is at rest due to irregular curvature of the cornea or lens surface. All-age data on the prevalence and types of astigmatism is not available in Bhutan. This study was carried out to determine the prevalence and determinants of astigmatism in the Central Regional Referral Hospital (CRRH) of Bhutan. Methods: This was a cross- sectional study done between November 2021 and August 2022 in CRRH with 302 participants. Routine visual acuity testing and refraction were done for all the individuals availing ophthalmic services and type of astigmatism was diagnosed. Results: The overall prevalence of astigmatism in individuals availing ophthalmic services at CRRH was found to be 4.18% and the most common types of astigmatism were compound myopic, with-the-rule (WTR) and mild astigmatism. Conclusion: Prevalence of astigmatism was found to be low in individuals availing ophthalmic services at CRRH. The most common types of astigmatism were compound myopic, WTR and mild astigmatism.